Analisis Elemen Visual dan Akustik Panel Bambu Betung pada Ruang Kerja Kreatif - Oky Setiawan; Nurul Fitriana Bahri; Nur Sabariah; Ahmad Riyadi Swandhani (LPPM STIKI Malang, 2025)
Bamboo has long been used in various aspects of design and architecture due to its flexibility, strength, and eco-friendly nature. As a readily available natural material with high aesthetic value, bamboo has great potential for various applications, including as an acoustic material. One type of bamboo that possesses ideal characteristics for this purpose is betung bamboo, which has a large-diameter stem and fibers capable of effectively absorbing sound. This study aims to explore the utilization of betung bamboo as an acoustic material in creative workspaces, particularly for professionals in visual communication design and multimedia. The method used is a mixed-method approach, incorporating qualitative analysis of the aesthetics and texture of bamboo along with quantitative testing of the effectiveness of bamboo panels in reducing noise. The results indicate that betung bamboo panels can absorb up to 97% of sound at specific frequencies, making them an ideal solution for multimedia production studios and graphic design spaces. Additionally, the visual elements of these panels enhance the interior aesthetics of workspaces, support visual identity, and improve user comfort. With these advantages, betung bamboo not only provides functional benefits as an acoustic material but also serves as a design element that seamlessly integrates with the modern workspace concept, combining aesthetics with efficiency.